Food form and portion size affect postprandial appetite sensations and hormonal responses in healthy, non-obese, older adults - Leidy, Heather J. (Obesity (Silver Spring), 2009)
Data are limited concerning the dietary factors that influence appetite control in older adults. This study examined the effects of food form (FF) and portion size (PS) on appetite in 43 older adults (age: 72±1 y; BMI: 25.6±0.3 kg/m(2)). Subjects were assigned to groups based on PS of the test-meal (12.5% (n=18) vs. 25% (n=25) of estimated energy need). Subjects randomly consumed, on 2 separate days, the respective solid (S) or beverage (B) test-meal. Appetite sensations and hormonal responses were measured over 4 h. Main effects of FF (p<0.05) and/or PS (p<0.05) were observed for each appetite sensation. Postprandial hunger and desire to eat were greater following B vs. S and between 12.5% vs. 25%, whereas fullness was lower after B vs. S (p<0.05). Main effects of FF and/or PS were observed for glucose, insulin, and ghrelin. Postprandial glucose and insulin concentrations were lower after B vs. S and between 12.5% vs. 25% (all comparisons, p<0.05) while B led to greater 4-h ghrelin vs. S (p=0.09). No main effects were observed for GLP-1 or CCK. When adjusting for age, FF remained significant for postprandial hunger and fullness; PS remained significant for postprandial glucose. Greater hunger and reduced satiety with accompanying glucose, insulin, and ghrelin following the beverage vs. solid meals, and to some extent, in smaller vs. larger portions suggest that appetite control is influenced by food form and portion size in older adults. These findings may enhance the development of appropriate dietary strategies to help regulate energy balance.